DETERMINANT FACTORS OF BLACKBERRY PURCHASE INTENTION - Reni Diah Kusumawati; Dessy Hutajulu (Jurnal Ilmiah Ekonomi Bisnis, 2012)
Development of science and technology enable people to communicate each others.Companies are competing to produce quality products at an affordable price, as well asthe brand that is easily remembered by consumers, taking into account the environment inwhich the product will be marketed. This study aimed to assess the effect of product,price, brand, and the environment on consumer purchase intention. The study populationsare students, with a sample of 153 respondents. Data obtained through a questionnaire,and then analyzed with multiple regressions. The results showed that simultaneously,product, price, brand, and environment influence on purchase intention.Key Words: Product, Advertising, Brand, Environment, Purchase Intention.